Analysis of the Influence of Internet Use on the Occurrence of Stress Among Female Adolescents at SHS 7 Palu - Noviana, Riri; Rahman, Abd; Sridani, Ni Wayan; Nur, Rosmala; Fauzan, Fauzan (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Around 68% of adolescents experience internet addiction linked to stress, anxiety, and depression. Initial observations of five students in Palu also showed that high internet use triggered symptoms such as anxiety and sleep disturbances. Objective: To analyze the influence of internet use on stress among female adolescents at SHS 7 Palu. Methods: This cross-sectional study involved all 275 female students selected through total sampling, with data analyzed using multiple linear regression. Results and Discussion: All variables significantly affected stress: internet use duration (t = 2.369; Sig = 0.019), social media use (t = 5.003; Sig = 0.000), cyberbullying (t = 4.060; Sig = 0.000), and online gaming (t = 4.978; Sig = 0.000). Conclusion: Longer internet use, higher social media activity, frequent cyberbullying, and increased online gaming all raise stress levels. Online gaming had the strongest influence, contributing 6.91% to stress.